The economic impact of COVID-19 and the rise of artificial intelligence: A comprehensive analysis - Bengana, Ismail; Mili, Khaled; Mehaouat, Labidi Hocine; Bounsiar, Abdenour; Cherbi, Mohammed Lamine (Edelweiss Applied Science and Technology, 2024)
This paper offers a comprehensive analysis of the global economic impact of the COVID-19 pandemic, examining the diverse responses and precautionary measures adopted by nations worldwide. It also delves into the trans-formative role of artificial intelligence (AI) in health surveillance and its implications for economic dynamics. AI, a key driver of the Fourth Industrial Revolution, is undergoing rapid evolution, prompting discussions on its benefits and challenges. Despite varying perspectives, its indispensability in modern society is acknowledged, with AI poised to drive societal transformation and restore global equilibrium. The study also highlights the active engagement of Arab countries, including Bahrain, in the AI landscape.